Role of transbronchial lung cryobiopsy in diagnosing pulmonary alveolar proteinosis—a five-case series - Vimal Raj Ramachandran; Hsu-Yuan Chen; Yu-Chu Kuo; Wen-Chien Cheng; Biing-Ru Wu; Wei-Chih Liao; Chia-Hung Chen; Chih-Yen Tu (The Egyptian Journal of Bronchology)
Abstract Pulmonary alveolar proteinosis (PAP) is a rare, diffuse lung disease marked by the accumulation of PAS-positive proteinaceous material within distal airspaces. Diagnostic procedures include bronchoalveolar lavage, transbronchial lung biopsy (TBLB), and surgical lung biopsy (SLB). Recently, transbronchial lung cryobiopsy (TBLC) has emerged as a promising technique for diagnosing parenchymal lung diseases. This case series investigates the efficacy of TBLC in diagnosing PAP and compares it to traditional TBLB methods.